Prevalence of Gun Carrying and Gun Violence Victimization and Perpetration Among a Nationally Representative Sample of U.S. Youth and Young Adults - Bruce G. Taylor, PhD; Kimberly J. Mitchell, PhD; Heather A. Turner, PhD; Jackie Sheridan-Johnson, MPH; Elizabeth A. Mumford, PhD (AJPM Focus)
Introduction: Guns were one of the leading causes of death in children and youth aged 0–24 years in the U.S. over the last decade, with large variations by sex, race, region, and income. This paper examines the rates of gun involvement for a group of youth and young adults in the U.S. from ages 10 years to 34 years across major demographic and background factors. Methods: This is a cross-sectional nationally representative survey of participants recruited through an ongoing national research panel. Completed surveys were collected from 5,311 participants from September 2023 to January 2024. Results: Lifetime rates for carrying guns were 26.7%, gun violence victimization rates were 9.5%, and gun violence perpetration rates were 3.3%. High levels of past-year involvement with guns and gun violence were observed, with 13.9% carrying guns, gun violence victimization of 2.5%, and gun violence perpetration of 0.9%. Even more concerning, data indicate that 7.6% of the participants reported carrying a gun before age 18 years, 5.2% experienced gun violence victimization, and 1.8% perpetrated gun violence. Gun carrying and violence were higher by demographics, with a statistically significant difference for all demographic subgroups on at least 1 gun outcome. Conclusions: High levels of exposure to guns and gun violence are experienced among a nationally representative population of young Americans, with rates varying considerably by demographic factors. On the basis of these demographic disparities in gun involvement, more work is needed to address community and other risk and protective factors across different levels of the social ecology, such as structural inequities associated with gun violence.